PROBLEMS AND PROSPECTS OF INTERMEDIARY METABOLISM CORRECTION IN PATIENTS WITH VASCULAR COMORBIDITY - S. A. Rumyantseva; R. G. Oganov; V. A. Stupin; E. V. Silina; A. S. Orlova; S. B. Bolevich; V. V. Afanasev; E. N. Kabaeva; S. A. Volik (Рациональная фармакотерапия в кардиологии)
Disorders of intermediary metabolism in the glycolysis cycles and fatty acids oxidation play a major role in heart and brain lesions of vascular origin. Features of the free-radical processes in various forms of vascular disease are presented. Differences within the free-radical processes reflecting the severity of tissue energy deficit are shown in stroke patients with concomitant ischemic heart disease, atrial fibrillation, and diabetes mellitus. Various aspects of the treatment of patients with vascular comorbidity are presented with the focus on correction of intermediary metabolism disorders. Complex energy correcting therapy including beta-oxidation blocker (meldonium) is discussed.